Nursing diagnoses in persons with HIV/aids: an approach based on Horta's conceptual model - Juliana de Oliveira Faria; Girlene Alves da Silva (Universidade Federal do Ceará, 2013)
This study aims at identifying nursing diagnoses in hospitalized persons with HIV/AIDS. It is a cross-sectional study carried out with 30 patients admitted at an infectious and parasitic disease clinic inside a teaching hospital in the state of Minas Gerais from March to September 2011. In order to identify the diagnoses, the NANDA Taxonomy II system was applied, together with an instrument based on Horta's conceptual model. The most common nursing diagnoses were: ineffective protection (100%), risk of vascular trauma (86.7%), imbalanced nutrition - less than body requirements (76.7%), impaired physical mobility (53.3%) and acute pain (53.3%). These diagnoses are relevant to manage the planning of nursing interventions towards the actual requirements with the purpose of promoting better health conditions to these patients.